The Role Of The Family Environment In The Formation Of The Personality Of The Preschool Child - Dilnoza Abdurashidovna Mutalova (Euro Asian Journal Publishing, 2024)
In this article, the current problems of the role of the family environment in the development of the personality of a child of kindergarten age are highlighted. The family processes, volitional-emotional qualities and psychological characteristics of preschool children are described. At the same time, the important aspects of relationships with children in the family are revealed.
Keywords: dequat; sympathy; behavior regulator; stimulant